2019
DOI: 10.1039/c9cp03246k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and kinetic studies of OH-initiated atmospheric oxidation of methoxyphenols in the presence of O2 and NOx

Abstract: Methoxyphenols, as the main products and tracers of biomass burning, have been demonstrated to play an important role in the formation of secondary organic aerosols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…Alternatively, carbon loss can also be explained by initial H-abstraction from the methoxy group followed by O 2 binding and the elimination of formaldehyde in the reductive NO atmosphere. 50 Neither of those byproducts, however, have been experimentally detected that the exact mechanism could have been unequivocally confirmed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, carbon loss can also be explained by initial H-abstraction from the methoxy group followed by O 2 binding and the elimination of formaldehyde in the reductive NO atmosphere. 50 Neither of those byproducts, however, have been experimentally detected that the exact mechanism could have been unequivocally confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested very recently by density functional theory (DFT) calculations that the [Ar–OH] • adduct with OH attached at position 2 is most favorable. 50 Another study showed that although it is theoretically feasible that OH binds to any aromatic C-atom in GUA, giving the corresponding isomeric [Ar–OH] • adducts and products, the OH attack to the hydroxyl-bearing carbon atom and to positions 2 and 4 are slightly more favorable as to the other C-atoms. 24 Moreover, our study shows that carbon loss is facilitated at high RH, which further implies the involvement of water molecules in the process of methoxy group release, possibly yielding methanol and the OH radical instead of the methoxy radical.…”
Section: Resultsmentioning
confidence: 99%
“…Phenoxy radicals generally derive from OH reaction with phenolic molecules and both NO and O3 compete with NO2 for reaction with phenoxy radicals; products from reaction with NO and O3 are not well established (Vereecken, 2019). The importance of the OH-aromatic adduct + NO2 pathway to nitro-aromatic formation is suggested as small for species such as toluene and phenol owing to efficient reaction with O2 (Atkinson et al, 1992;Vereecken, 2019), although has been proposed as the major pathway for nitro-aromatic formation from guaiacol and similar species (Lauraguais et al, 2014;Sun et al, 2019).…”
Section: Chamber Photochemical Model Descriptionmentioning
confidence: 99%
“…Laboratory measurements can help provide the mechanistic understanding necessary to comprehensively interpret the field observations. Most laboratory studies investigating photochemical aging effects on optical properties, and in particular light absorption, of BB particles have done so for only a small number of individual fuel types or burn conditions and often for particles alone rather than smoke (e.g., Saleh et al, 2013;Sumlin et al, 2017;Tasoglou et al, 2017;Wong et al, 2017;Kumar et al, 2018). Thus, while these studies have proven insightful, the limited number of fuels and conditions considered makes extending the observations to the atmosphere thus far challenging.…”
Section: Introductionmentioning
confidence: 99%